Components of dual-purpose cattle production system in the Nangaritza and Palanda Cantons, Zamora Chinchipe province, Ecuador - Chuquirima R., Darwin (2023)
The improvement of the Agricultural Production Units (UPA) in Ecuador depends on the knowledge of the needs of the farmers for the approach of suitable alternatives and technology transfer. The aim of this study was to identify the components of the double-purpose cattle production system in two cantons of the Zamora Chinchipe province. Thirty farmers were interviewed from the Nangaritza canton and 65 from Palanda, with a questionnaire that considered social, technical and economic aspects. In both cantons family labour predominates and most own the land. Moreover, 53 and 73% of the UPAs of Nangaritza and Palanda, respectively, have between 5 and 50 ha, where they mainly cultivate Merkeron grass (Setaria sphacelata). The average number of heads per UPS is 43 and 37 in the cantons of Nangaritza and Palanda, respectively. In the economic aspect, the livestock products are sold outside the UPA and farmers finance their activities with credits from the State Bank. It is concluded that cattle production in both cantons are based on extensive systems, that although there is technical assistance, still there are deficiencies that could be improved if technologies are implemented according to the particularities of the farmers.